The downs and ups of mark-ups - Leif Brubakk; Kåre Hagelund (Norges Bank, 2023)
Based on sectoral National accounts data and estimates of the implicit rental rate of capital, we calculate price mark-ups for 42 Norwegian industries for the period 1980-2019. The results indicate a broad-based increase in mark-ups over the sample period, with an average increase of roughly 20 percentage points. Taken at face value, the secular rise in mark-ups have added almost 0.5 percentage points to GDP inflation each year since 1980. As part of the analysis, we also trace out movements in factor shares. Our results indicate a widespread decline in capital shares, and more so than for labor shares. Hence, our findings cast doubt on factor substitution as an important explanation for the decline in the aggregate labor share and instead point to increased corporate market power as the main culprit.
hdl:11250/3050870
Keywords: 330; Mark-up Pricing; Marktmacht; Industrie; Norwegen